The role of fundamental rights in the environmental case law of the CJEU - Jasper Krommendijk; Dirk Sanderink (European Law Open, 2023)
There has been a turn to fundamental rights in environmental and climate cases before national and international courts in recent years. We know very little whether there has been such a turn in relation to European Union (EU) law before the Court of Justice of the European Union (CJEU). The CJEU occupies an increasingly relevant position in this nexus between environmental law and human rights because of strong and effective EU enforcement mechanisms, the abundance of specific EU secondary environmental law, the growing role of fundamental rights since 2009 and the self-standing provision on the environment in Article 37 of the Charter. An analysis of the case law, nonetheless, shows that Charter rights that can be used as ‘swords’ in the interest of environmental protection have so far played only a limited role. After explaining the absence of a rights turn, we argue that such a turn is warranted before the CJEU as well, also from a legal perspective. This article examines two potential avenues. The CJEU can derive positive obligations from relevant Charter provisions, including Articles 2 (right to life) and 7 (right to respect for private life and the home) of the Charter, or it can rely more extensively on Article 37 as a tool for interpreting primary and secondary EU law in an environmentally friendly way.